Anthropometric Parameters as Predictors of Peak Expiratory Flow Rate in Central Indian Children 5-15 Years - Pawar, Sachin; Shende, Vinod; Waghmare, Satish; Jivtode, MT (Journal of Diagnostics, 2014)
The development of pulmonary function and growth of physical parameters are concurrent in children. Hence, measurement of lung function is essential for evaluation of physical development of children and adolescent with respiratory disease. A cross sectional study was conducted on 200 primary, middle and high school children of 5-15 years. Their anthropometric parameters and peak expiratory flow rate (PEFR) were recorded and multiple regression equations for predicting PEFR from anthropometric variables were derived. Highly significant positive correlation (P<0.01) was observed between all the anthropometric and pulmonary parameters. Significantly high R2 values were found when age, height, weight, chest circumference, BSA and arm span were used as independent variables in the regression analysis. Thus, this study establishes reference standards for predicting PEFR in normal healthy children residing in Central India.